Pelatihan Penulisan Karya Tulis Ilmiah untuk Meningkatkan Kompetensi Profesional Guru - Fuad, Ramli; Gita, Yuda; Sukri, Akhmad; Adia, Muhamad (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2021)
The Community Service Program (CSP) which is carried out aims to increase the willingness of teachers to write scientific papers, improve the ability of teachers to write scientific papers, and improve the ability to search references in various sources. The implementation of PKM is preceded by providing information to the principal about the training activities to be carried out, giving invitations to teachers who will be training participants, carrying out training, and making reports on the results of the implementation of activities. The materials presented during the training were: 1) The urgency of writing scientific papers to improve the career and knowledge of educators; 2) Strategies for writing scientific papers in proceedings and journals; 3) Various scientific journals; and 4) Systematics of proceedings and journal articles. Participants also get guidance on writing scientific papers in tutorial activities and practice writing scientific papers. The training participants were 23 elementary school teachers in Sumber Manjing Wetan District. After the training, the results obtained are: 1) an increase in the willingness of teachers to write scientific papers; 2) an increase in the ability of teachers to write scientific papers; 3) an increase in the ability to search references in various sources; and 4) participants know about various scientific journals at PGRI University Kanjuruhan Malang which can be used to publish their scientific works.